Analisis Tren Pendaftaran Siswa Menggunakan Big Data di Yayasan Pendidikan Raksana Medan - Nadya Septiani Nadya; Muhammad Iqbal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Yayasan Pendidikan Raksana Medan is an educational institution encompassing SMP, SMA, SMK-1, and SMK-2 levels. With an increasing number of students each year, analyzing student enrollment data has become crucial for strategic planning and decision-making. This study aims to analyze student enrollment trends using a Big Data approach to identify enrollment patterns, study program preferences, and factors influencing the number of applicants. The data used includes enrollment information from the past five years, such as demographic data, program choices, and enrollment timing. The analysis was conducted using data mining methods and data visualization to identify specific trends and patterns. The results of the study indicate a significant increase in applicants to vocational programs, with the majority of applicants coming from areas around Medan. These findings are expected to assist Yayasan Pendidikan Raksana Medan in improving marketing strategies and curriculum adjustments based on student and community demand